2007
DOI: 10.1016/j.jsbmb.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain aromatase: Roles in reproduction and neuroprotection

Abstract: It is well established that aromatization constitutes an essential part of testosterone's signaling pathway in brain and that estrogen metabolites, often together with testosterone, organize and activate masculine neural circuits. This paper summarizes the current understanding regarding the distribution, regulation and function of brain aromatase in mammals. Data from our laboratory are presented that highlight the important function of aromatase in the regulation of androgen feedback sensitivity in non-human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 109 publications
1
79
0
2
Order By: Relevance
“…Forlano and Bass, 2005b), paralleling the known data for mammals (e.g. Roselli, 2007). Thus, the development of the testicular gland and concomitant surge in gonadal androgens may be the key factor inducing both the morphologic and behavioral changes associated with tactic transition.…”
Section: Brain Aromatase Activitysupporting
confidence: 74%
See 1 more Smart Citation
“…Forlano and Bass, 2005b), paralleling the known data for mammals (e.g. Roselli, 2007). Thus, the development of the testicular gland and concomitant surge in gonadal androgens may be the key factor inducing both the morphologic and behavioral changes associated with tactic transition.…”
Section: Brain Aromatase Activitysupporting
confidence: 74%
“…In vertebrates, it is well established that aromatase plays a key role both in sexual differentiation and in the expression of reproductive behaviors (e.g. Ball and Balthazart, 2004;Baum, 2003;Roselli, 2007;Forlano et al, 2006). In fish, two aromatase isoforms have been described, one preferentially expressed in the ovary (coded by the CYP19a gene) and one preferentially expressed in the brain (coded by the CYP19b gene) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we observed that sildenafil significantly inhibited aromatase activity in a dose-dependent manner, inducing about 38% of decrease at 1 µM of concentration (Table 2). Moreover, on the basis of the relevance of aromatase protein in neural cells, where estrogens have been demonstrated to act as neurotransmitters [48] and to be neuroprotective [49], as additional model of analysis we used the neural progenitor ST14A cell line. Cells were transfected with an aromatase expression vector and protein expression was confirmed by Western blotting analysis ( Figure 6).…”
Section: Effect Of Sildenafil On Full-length Aromatase Activity In Cellsmentioning
confidence: 99%
“…Notably, the male hormone testosterone is readily converted to 17b-estradiol by aromatase in neurons and astrocytes, which suggests that endogenous androgen levels in males may affect 17b-estradiol-mediated protection after SCI (Roselli, 2007). Testosterone in males is physiologically secreted by the testes and adrenal glands, and acts primarily via androgen receptors.…”
mentioning
confidence: 99%